A turtle's tale Sammy's adventures - Stassen, Ben.; Lowenthal, Yuri.; Griffith, Melanie, 1957-; Griffin, Kathy, 1960-; Curry, Tim.; Anderson, Anthony, 1970-; Keach, Stacy; McCarthy, Jenny, 1972-; Studio Canal; Vivendi Entertainment (Firm) ([United States] : Studio Canal ; [Universal City, Calif.] : Distributed by Vivendi Entertainment, 2011)
A sea turtle hatched in 1959 spends the next fifty years swimming the oceans, searching for the love of his life, and watching how global warming changed the planet.
Music, Ramin Djawadi.
Voices: Yuri Lowenthal, Melanie Griffith, Kathy Griffin, Tim Curry, Anthony Anderson, Stacy Keach, Jenny McCarthy.
Not rated.
DVD, widescreen format ; Dolby digital 5.1 ; NTSC 1.
Closed-captioned.
Keywords: Sea turtles -- Juvenile films; Love -- Juvenile films; Global warming -- Juvenile films; Animated films; Children's films; Animal films; Fiction films